2017
DOI: 10.1002/ajoc.201700251
|View full text |Cite
|
Sign up to set email alerts
|

Aryne–Imine–Aryne Coupling Reaction via [4+2] Cycloaddition between Aza‐o‐Quinone Methides and Arynes

Abstract: A direct method for the synthesis of acridane derivatives based upon a 2:1 coupling reaction between arynes and imines was developed. The reaction proceeds through formation of transient aza‐ortho‐quinone methides arising from a net [2+2] cycloaddition between arynes and imines. Introduction of steric bulk into an imine carbon has proven to be vital for this facile coupling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 30 publications
1
14
0
2
Order By: Relevance
“…Notably, the aryne‐imine‐aryne coupling reaction was described to proceed through the formation of aza‐ ortho ‐quinone methide intermediate III , which then reacts with the corresponding aryne to form a product possessing an acridane core ( Scheme 3, pathway a ) [7] . However, in the case of phenanthryne, the formation of 1,2‐dihydrobenzoazete II and intermediate III might be impacted by unfavorable steric interactions between the mesityl group and the extended system of the phenanthrene moiety.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, the aryne‐imine‐aryne coupling reaction was described to proceed through the formation of aza‐ ortho ‐quinone methide intermediate III , which then reacts with the corresponding aryne to form a product possessing an acridane core ( Scheme 3, pathway a ) [7] . However, in the case of phenanthryne, the formation of 1,2‐dihydrobenzoazete II and intermediate III might be impacted by unfavorable steric interactions between the mesityl group and the extended system of the phenanthrene moiety.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the aryne-imine-aryne coupling reaction was described to proceed through the formation of aza-ortho-quinone methide intermediate III, which then reacts with the corresponding aryne to form a product possessing an acridane core (Scheme 3, pathway a). [7] However, in the case of phenanthryne, the formation of 1,2-dihydrobenzoazete II and intermediate III might be impacted by unfavorable steric interactions between the mesityl group and the extended system of the phenanthrene moiety. This increased steric bulk around the reactive center of phenanthryne could lead to a divergent mechanism of the aryne-imine-aryne coupling, which involves the nucleophilic attack of the imine at the phenanthryne, leading to the generation of intermediate I.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Notably, according to the proposed mechanism for the aryne–imine–aryne coupling, the imine requires sterically demanding substituents near the C-terminus to prevent an undesired 6π-electrocyclization. 20 Therefore, imines with di- ortho -substituted phenyl groups (R 2 ) were synthesized with the consequence that the acridinium salts prepared utilizing this two-step strategy possess a sterically shielded C9 position to further prevent photobleaching via nucleophilic attack or light-promoted radical–radical couplings. 22…”
Section: Table 1 Scope and Photophysical Properties Of ...mentioning
confidence: 99%
“…In 2017 H. Yoshida and co‐workers showed that trapping of the aza‐ ortho ‐quinone methide intermediate 3c to form 2:1 imine:benzyne adducts 4c was possible when benzyne was used in molar excess. This mode of reactivity prevails when the aryl moieties are more highly substituted, presumably slowing the electrocyclization of 3c to 3d .…”
Section: Introductionmentioning
confidence: 99%